Analisis Dampak Distribusi Dana Zakat terhadap Masyarakat Miskin dan Kepuasan Muzaki di Provinsi Jambi - Muhammad Qodri; Rafiqy Rafiqy (ZAWA: Management of Zakat and Waqf Journal, 2022)
This study analyzes the impact of zakat distribution on the poor and the satisfaction of muzakki in Jambi Province. Zakat has the power to share income, especially in creating justice and social welfare. Indonesia with a large Muslim population has great potential to receive zakat. This is not accompanied by the ability to manage zakat in realizing zakat income which is not yet optimal. In general, the purpose of this research is to create the best model of zakat empowerment based on Sharia principles which is expected to be an effective way to overcome poverty and its effect on muzakki satisfaction in paying zakat. The results of the study stated that zakat had a significant effect on mustahiq who received zakat funds of 71.99% and gave satisfaction to muzakki in issuing zakat of 75.26%.